Composite Sliding Mode Control of High Precision Electromechanical Actuator Considering Friction Nonlinearity - Bangsheng Fu; Hui Qi; Jiangtao Xu; Ya Yang (Actuators, 2022)
Friction nonlinearity, which is common in electromechanical actuator (EMA) systems, leads to undesired dynamic responses such as “flat top”, low-speed crawl, which brings challenges to high precision attitude control of flight vehicles. In order to improve the robustness of the actuator control system under friction nonlinearity, and suppress the chattering caused by high gain of sliding mode control (SMC), a composite SMC scheme based on modified extended state observer (MESO) is proposed. Nonlinear MESO is adopted for estimating the nonlinear friction dynamics, unmodeled disturbance, and external real-time load dynamics so as to compensate for their adverse effect. At the same time, in order to improve the robustness of EMA, and reduce the tracking error of the servo system, SMC is adopted to ensure the tracking error convergence in a finite time. The stability of the proposed method is proved, and the effectiveness is verified by simulations.